Modeling and simulation of multi-plane Electrical Capacitance Tomography sensor for flow imaging by using Finite Element Analysis - Shafquet, A. (IEEE Computer Society, 2014)
This research work is mainly focused on modeling and simulation of Electrical Capacitance Tomography (ECT) sensor which comprises of 12 electrodes that are fabricated externally. The arrangement of electrodes is in the form of multi-plane (i.e. single and twin-plane electrodes). The Finite Element Method (FEM) can be utilized to simulate and compute capacitance values. This simulation method can provide sensitivity distribution and also helpful in obtaining the permittivity distribution for multi-phase flow. This paper focuses on the need for field simulation in the design and analysis of multi-electrode capacitance sensors for tomographic flow imaging. However, the real sensors are 3D but mostly a cross-section is modeled in 2D. The governing equations and the modeling approach for 2D single- and twin-plane ECT sensor using Electromagnetic Module of COMSOL Multiphysics are discussed in this manuscript. The single- and twin-plane simulation has been done for velocity and volume measurement respectively. An image reconstruction algorithm for ECT have presented in this work is based on the FEM. Simulation results are duly verified by an experimental data that has been obtained from the calculation of gas-oil two-phase flow. Â© 2014 IEEE.